Botkin Hospital Transplant Program: 100 solid organ transplantations - A. V. Shabunin; I. P. Parfenov; M. G. Minina; P. A. Drozdov; I. V. Nesterenko; D. A. Makeev; O. S. Zhuravel (Вестник трансплантологии и искусственных органов)
Objective: to evaluate the first results of the Botkin Hospital transplant program. Materials and methods. From June 2018 to October 2019, 100 solid organ transplants were performed at the Botkin City Clinical Hospital. Out of the 100 transplantations, 72 were kidney transplants (average age of recipients was 45.65 ± 11.35 years, HLA match averaged 2.09 ± 1.03) and 28 were liver transplants (average age of recipients was 50.14 ± 7.62 years, average MELD was 17.78 ± 3.28 (14–34). Results. After transplantation, there was no 30-day mortality. Postoperative complications following kidney transplantation were established in 11 patients (15.2%). In 3 patients (4.3%) – suppuration of postoperative wound, in 2 patients (2.8%) – hematomas in the area of the postoperative suture during hemodialysis, in 5 patients (6.9%) – retroperitoneal lymphocele, in 1 patient (1.4%) – urosepsis. There were 4 cases (5.5%) of acute rejection, 3 cases (4.2%) of humoral rejection, and 1 case (1.3%) of cellular rejection. Early postoperative complications following liver transplantation were detected in 2 patients (7.2%). In one patient – hematoma under the right lobe of the liver on the 1st day after surgery, the diaphragm was the source of bleeding, in one patient – ascites leakage through postoperative sutures, which required relaparotomy. In 2 patients (7.2%), postoperative complications were found in the separated postoperative period. In one case, of choledochocholedochal anastomotic stricture – stricture stenting was performed with coated nitinol stent. In another case, acute adhesive intestinal obstruction, which required laparotomy, adhesiolysis. Conclusion. Implementation of the transplantation program in multidisciplinary hospitals can boost transplant care in a district and improve the treatment results of patients with terminal organ damage.